Penerapan Majemen Mutu Pendidikan dan Total Quality Management (TQM) untuk Meningkatkan Mutu Pendidikan di Kelompok Bermain ( KB ) Al Muttaqin - Wahyuni, Tris; Miyono, Noor (Jurnal Inovasi Pembelajaran di Sekolah, 2024)
The aim of this research is to explain the planning, organization, implementation and control of Education Quality Management and TQM in improving the quality of KB Al Muttaqin education. The method used in this research uses a qualitative method by conducting interviews with Foundation Management, school principals and teachers as well as other necessary administrative data. Implementation and development of education quality management policies at KB AL Muttaqin and TQM to improve the quality of school education through an integrated quality management strategy that focuses on customers. A systematic approach is needed, a sustainable activity program and prioritizing the quality of education through the use of human resources as well as facilities and infrastructure to support the achievement of the activity program implemented by KB AL Muttaqin. The education quality management system and TQM to improve the quality of education are implemented within the Al Muttaqin KB environment including planning, organizing, implementing and controlling.